Utilizing Probiotics for the Prevention and Treatment of Gastrointestinal Diseases - Milner, Erin; Stevens, Benjamin; An, Martino; Lam, Victoria; Ainsworth, Michael; Dihle, Preston; Stearns, Jocelyn; Dombrowski, Andrew; Rego, Daniel; Segars, Katharine (Frontiers in Microbiology, 2021)
Probiotics are heavily advertised to promote a healthy gastrointestinal tract and boost the immune system. This review article summarizes the history and diversity of probiotics, outlines conventional in vitro assays and in vivo models, assesses the pharmacologic effects of probiotic and pharmaceutical co-administration, and the broad impact of clinical probiotic utilization for gastrointestinal disease indications.